Design of a Dual-Band Dielectric Resonator Antenna Array for Millimeter-Wave Communication - Wang, Ya-Xing; Chen, Zhe; Yuan, Tao (IEEE antennas and wireless propagation letters, 2023)
This paper presents a dual-band dielectric resonator antenna (DRA) with a large frequency ratio at millimeter-wave band. A large frequency ratio of 2.36 is formed by the TE 111 mode and TE 131 mode working at 16 GHz and 38 GHz, respectively. These two modes of DRA are excited by a microstrip-fed slot. A 1×4 DRA array is then constructed to achieve high gain in the millimeter-wave range. In addition, this design also features easy fabrication and wideband characteristics achieved through the use of printing circuit board (PCB) technology. The impedance bandwidths of 13.3 - 19 GHz (35.3%) and 36.3 - 40 GHz (9.7%), and the gain of 10.6 and 14.2 dBi can be realized in these two bands, respectively. The good agreement between measurement and simulation suggests that this design has promising potential for application in millimeter-wave communication.